Declarative memory and skill-related knowledge: Evidence from a case study of amnesia and implications for theories of memory. Issue 3 (18th May 2016) - Gregory, Emma; McCloskey, Michael; Ovans, Zoe; Landau, Barbara
ABSTRACT: Theoretical and empirical studies of memory have long been framed by a distinction between declarative and non-declarative memory. We question the sharpness of the distinction by reporting evidence from amnesic L.S.J., who despite retrograde memory losses in declarative knowledge domains, shows sparing of declarative knowledge related to premorbid skill (e.g., playing an instrument). We previously showed that L.S.J. had severe losses of retrograde declarative knowledge across areas of premorbid expertise (e.g., artists of famous works) and everyday knowledge (e.g., company names for logos). Here we present evidence that L.S.J. has sparing of what we call skill-related declarative knowledge, in four domains in which she had premorbid skill (art, music, aviation, driving). L.S.J.'s pattern of loss and sparing raises questions about the strict separation between classically-defined memory types and aligns with a recent proposal by Stanley and Krakauer [2013. Motor skill depends on knowledge of facts. Frontiers in Human Neuroscience, 7, 1-11].